2020
DOI: 10.7762/cnr.2020.9.2.107
|View full text |Cite
|
Sign up to set email alerts
|

Breakfast Intake Effect on the Association between Fast-Food Consumption and the Risk of Obesity and Dyslipidemia in Korean Adults Aged 20–39 Years Based on the Korea National Health and Nutrition Examination Survey IV 2013–2014

Abstract: We investigated the association between fast-food (FF) consumptions and the risk of overweight/obesity and dyslipidemia in Korean adults (20-39 years) based on the Korea National Health and Nutrition Examination Survey (2013-2014). We also examined the effect of breakfast intake on the risk of overweight/obesity and dyslipidemia according to their frequencies of FF consumption. FF consumption was categorized into 3 groups: < 1 time/ month (n = 79); 1-3 times/month (n = 1,173); and ≥ 1 time/week (n = 474). Peop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Several publications have explored the relationship between skipping breakfast and serum TC, primarily focusing on adolescents ( 72 – 74 ). However, only one study from Korea reported a significantly higher level of serum TC in adults who skipped breakfast ( 75 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several publications have explored the relationship between skipping breakfast and serum TC, primarily focusing on adolescents ( 72 – 74 ). However, only one study from Korea reported a significantly higher level of serum TC in adults who skipped breakfast ( 75 ).…”
Section: Discussionmentioning
confidence: 99%
“…The spread of low-quality foods has anticipated the incidence of atherosclerosis and related complications with a parallel increase in plasma lipid levels [321,[357][358][359][360][361][362] Chronic kidney disease Proper cooking methods could reduce the excessive intake of minerals (e.g., potassium, phosphorus) and proteins frequently contained in fast food, ultra-processed and packaged food [363][364][365][366][367][368][369][370] Inflammation…”
Section: Obesitymentioning
confidence: 99%
“…Ultra-processed foods are characterized by low-quality and high-calorie density products; this diet comprises a substantial part of global nutrition due to the addictive taste, low cost and wide availability of these foods. In parallel with the increase in the incidence of metabolic syndrome, dyslipidemia and other cardiovascular risk factors, fast food and ultra-processed foods have become more prevalent in diets globally and are frequently associated with other unhealthy eating behaviors [358,359]. In recent years, younger generations [360,361] have been increasingly exposed to junk food such as processed red meats, fried foods and high-calorie meals rich in refined sugars and salt.…”
Section: Skipping Mealsmentioning
confidence: 99%
“…There are undeniably other adverse effects, such as cardiovascular disease, depression and hyperactivity. Obesity, though, is the most troublesome concern arising from the eating of fast food, especially for those residing in urban cities without daily exercise and in poor living conditions, (Egger & Dixon, 2014;Ahmed et al, 2019;Yoon et al, 2020). Fast food typically includes high cholesterol, high sugar, sodium, calories, and sometimes a high-fat content.…”
Section: Consumption Of Food By Childrenmentioning
confidence: 99%